2022
DOI: 10.7759/cureus.30721
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of Intravenous Insulin in Treatment of Patient With Diabetic Ketoacidosis: A Systematic Review and Meta-Analysis

Abstract: The most common acute hyperglycemic emergency is diabetic ketoacidosis (DKA). DKA is one of the leading causes of Type 1 diabetes (T1D) related deaths in people aged 30 and under. In this meta-analysis, the Overall use of IV insulin in patients with mild/moderate vs. severe diabetic ketoacidosis was compared in randomized controlled trial articles from January 2011 to December 2021 using EMBASE, Medline, and CENTRAL. Only 8 of 3258 studies met the inclusion criteria. This review shows that intravenous insulin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0
4

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 26 publications
1
4
0
4
Order By: Relevance
“…In coherence with the results from previous studies [2,28,30], in the present work, none of the patients exhibited biochemical and clinical signs suggestive of hypoglycemia, hypokalemia, and hyponatremia which is one of the important advantages of this alternative method [2,28,30]. While by using intravenous insulin, signi cant hypoglycemia and hypokalemia continue to be areas of concern [32].…”
Section: Discussionsupporting
confidence: 89%
“…In coherence with the results from previous studies [2,28,30], in the present work, none of the patients exhibited biochemical and clinical signs suggestive of hypoglycemia, hypokalemia, and hyponatremia which is one of the important advantages of this alternative method [2,28,30]. While by using intravenous insulin, signi cant hypoglycemia and hypokalemia continue to be areas of concern [32].…”
Section: Discussionsupporting
confidence: 89%
“…Adverse event profile of 3HP is considered favourable compared to alternative regimens in previous studies [9, 17]. The 3HP regimen is also considered superior to 9HP in terms of lower risk of hepatotoxicity [11].…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, there is growing recognition of advancing the inclusion and expansion in coverage of TPT services as a key priority for TB elimination and achieving global end TB targets by interrupting the chain of TB transmission [6, 8]. Newer TPT regimens, especially INH‐Rifapentine (3HP) are effective short course regimens with improved safety profile which have potential for widespread utilisation in high‐burden countries [9–11].…”
Section: Introductionmentioning
confidence: 99%
“…A recent systematic review demonstrated that the overall rate of improved hair loss was 56.60%, with a higher rate of improvement (65.80%) observed in the combined therapy group compared to the spironolactone monotherapy (43.21%). 50 In a retrospective study of 79 FPHL patients receiving an average dose of 100 mg of spironolactone daily, all patients noted stable or improved hair growth. However, patients with a Sinclair Score of 2.5 or higher noted greater improvement.…”
Section: Spironolactonementioning
confidence: 99%
“…51 Spironolactone at the dose of 100 mg or below is well tolerated. The reported adverse events are postural hypotension, lightheadness, breast tenderness, irregular menses, diuretic effects, electrolyte imbalances, mild nausea, vomiting, and scalp pruritus, 36,[50][51][52][53] Bicalutamide Bicalutamide is a novel AR antagonist with a much better safety and tolerability profile than flutamide. It is a nonsteroidal, pure antiandrogen with no estrogenic, no progesterone, no glucocorticoid, no mineralocorticoid, no diuretic effect, and no androgen activity.…”
Section: Medical Treatment For Aga Panchaprateep 259mentioning
confidence: 99%